Axonal transport of neural membrane protein 35 mRNA increases axon growth - Merianda, Tanuja T.; Vuppalanchi, Deepika; Yoo, Soonmoon; Blesch, Armin; Twiss, Jeffery L. (Journal of cell science, 2013)
Many neuronal mRNAs are transported from cell bodies into axons and dendrites. Localized translation of the mRNAs brings autonomy to these processes that can be vast distances from the cell body. For axons, these translational responses have been linked to growth and injury signaling, but there has been little information about local function of individual axonally synthesized proteins. In the present study, we show that axonal injury increases levels of the mRNA encoding neural membrane protein 35 (NMP35) in axons, with a commensurate decrease in the cell body levels of NMP35 mRNA. The 3′ untranslated region (3′UTR) of NMP35 is responsible for this localization into axons. Previous studies have shown that NMP35 protein supports cell survival by inhibiting Fas-ligand-mediated apoptosis; however, these investigations did not distinguish functions of the locally generated NMP35 protein. Using axonally targeted versus cell-body-restricted NMP35 constructs, we show that NMP35 supports axonal growth, and overexpression of an axonally targeted NMP35 mRNA is sufficient to increase axonal outgrowth.